Acts - Parsons, Mikeal Carl (Paideia commentaries on the New Testament, 2008)
Introduction -- Part I: Acts 1/7, the sense of a beginning -- Acts 1, the beginning of the church -- Acts 2, the miracle and meaning of Pentecost -- Acts 3:1/4:31, the healing of a lame man -- Acts 4:32/5:42, tensions within and without -- Acts 6/7, Stephen and the seven -- Part II: Acts 8/12, beyond Jerusalem : Philip, Saul, Peter, and others -- Acts 8 Philip : a man on a mission -- Acts 9:1/31 Saul and Ananias : conversion and call -- Acts 9:32/11:18 Peter : his words and deeds -- Acts 11:19/12:25, Barnabas, Peter, and Herod -- Part III: Acts 13/19, Paul's mission to the gentile world -- Acts 13/14, Paul's initial missionary campaign -- Acts 15:1/16:5, the Jerusalem Conference -- Acts 16:6/17:15. Paul in Macedonia -- Acts 17:16/18:17, Paul in Achaia -- Acts 18:18/19:41, Paul in Ephesus -- Part IV : Acts 20/28, Paul's farewell journey -- Acts 20:1/21:16, Paul's last journey to Jerusalem -- Acts 21:17/23:35, Paul in Jerusalem -- Acts 24/26, Paul before Felix, Festus, and Agrippa -- Acts 27/28, the sea voyage to Rome